THREE DIMENSIONAL MODELING OF SEDIMENT TRANSPORT UPSTREAM OF AL-BETERA REGULATOR-IRAQ - Sharif Khayyun, Thair; Nezar H. Mouhamed (Journal of Engineering and Sustainable Development, 2018)
This paper represents an analytical study, simulation (flow field and sediment movements), and estimation of the sediment deposition for the Al- Betera river reach upstream of Al-Betera regulator – Maysan Governorate–Iraq. Field measurements techniques and SSIIM Model were used for these purposes. A river reaches with a length of 4250m was chosen and divided into 17 cross-sections. The Model solves the Navier – stokes equations for calculating the water velocity with a k-ε model for predication the turbulence (shear stress). The Model is a stepping stone in the field of Computational Fluid Dynamics (CFD). The sediment rating curve was established by using the historical data (1984-2014) of the suspended sediment loads and river discharge which considers as a reference for researchers who are interested in the field of sediment transport. The plan form of river morphology was classified as a straight (1.07 sinuosity) for the period 1986, 2007and 2014. In this study, a new sediment load transport rate equation by using multiple linear regression analysis was developed. The results of the evaluation showed that the new model performs better than many Researchers [Ackers(1973), Yang(1996), Van Rijn(1987), Ariffin (2004), and Jassim (2012) ]. A graphical representation of 3D velocities was obtained by simulation and by using Power-law Scheme (x-y,y-z,x-z planes). Good agreements were found between the simulated and measured values of the flow velocity and sediment concentration in 3D for the selected 3 nodes in the y-direction and for 3 depths of flow ...